Avaliando o Impacto da Comunicação na Cobertura de Área com um Conjunto Dinâmico de Veículos Aéreos Não Tripulados - Ferreira, Antonio Pedro Santana; Sá, Alirio Santos de (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2025)
The multi-UAV area coverage problem concerns the coordinated action of UAVs to cover an area of interest, for example, mapping or collecting information from the entire area. In critical applications such as search and rescue, disaster mapping, and others, it is essential that the system allows for the inclusion of new UAVs, tolerates the failure or replacement of existing UAVs, and prevents potential communication failures from jeopardizing the mission. Therefore, it is crucial to develop area coverage solutions with dynamic sets of coordinated UAVs in unreliable communication environments to meet these types of applications. However, existing solutions that work with sets of UAVs either consider static sets or do not consider the possibility of communication failures. Therefore, developing solutions for critical area coverage missions remains a challenge. Consequently, in this paper, we address this problem by investigating the impact of communication on area coverage with a dynamic set of UAVs. The experimental evaluation considered area coverage applications based on static and dynamic sets of UAVs communicating over reliable and unreliable communication channels and equipped with underlying communication systems with different message detection and recovery capabilities. Performance was analyzed considering metrics related to mission execution speed and the ability to avoid redundant movement. The results show significant impacts on area coverage performance when we adopt message detection and recovery mechanisms. Furthermore, the analysis of the results shows that the appropriate combination of communication fault tolerance mechanisms at the application and communication system levels can enable complete area coverage with intermediate impacts on performance.